COOLFACADE - Alejandro Prieto Hoces (A+BE: Architecture and the Built Environment)
The thesis ‘COOLFACADE – Architectural integration of solar cooling strategies in the building envelope’ aims to shed light on the possibilities and constraints for architectural integration of solar cooling systems in façades, in order to support the design of climate responsive architectural products for office buildings as self-sufficient alternatives to conventional air-conditioning systems. Increasing cooling needs in the built environment present an important and complex challenge for the design of sustainable buildings and cities. Even though the first course of action should always aim to reduce energy consumption through saving measures and passive design, this is often not enough to avoid mechanical equipment altogether, particularly in the case of office buildings in warm climate contexts.